2023
DOI: 10.1038/s42003-023-04813-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuronopathic Gaucher disease models reveal defects in cell growth promoted by Hippo pathway activation

Abstract: Gaucher Disease (GD), the most common lysosomal disorder, arises from mutations in the GBA1 gene and is characterized by a wide spectrum of phenotypes, ranging from mild hematological and visceral involvement to severe neurological disease. Neuronopathic patients display dramatic neuronal loss and increased neuroinflammation, whose molecular basis are still unclear. Using a combination of Drosophila dGBA1b loss-of-function models and GD patient-derived iPSCs differentiated towards neuronal precursors and matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Moreover, the hippo signaling is interconnected with the Wnt signaling pathway and regulates both innate and adaptive immunity [ 86 ]. A recent study reported that a hyper-activation of hippo pathway alters the growth/death balance and may underlie the neuronal loss in neuronopathic Gaucher disease [ 87 ], which suggested the association between hippo pathway and neurological pain in FD [ 88 ]. In addition, other major partners in Hippo signaling are under-expressed in Fabry podocytes, such as LATS1 and YAP1 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the hippo signaling is interconnected with the Wnt signaling pathway and regulates both innate and adaptive immunity [ 86 ]. A recent study reported that a hyper-activation of hippo pathway alters the growth/death balance and may underlie the neuronal loss in neuronopathic Gaucher disease [ 87 ], which suggested the association between hippo pathway and neurological pain in FD [ 88 ]. In addition, other major partners in Hippo signaling are under-expressed in Fabry podocytes, such as LATS1 and YAP1 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients carrying L444P mutation exhibit a heterogenous phenotype 2 , including astrogliosis and neuronal loss 7 , 8 . However, it is still unclear what the underlying mechanism of the pathological features observed in the brains of GD patients is, as well as why there is heterogeneity among GD types 5 , 9 . A deeper understanding of the pathophysiology of GD will be invaluable in determining the factors contributing to the variability of its symptoms.…”
Section: Introductionmentioning
confidence: 99%